Disney Pixar : Cars. (New York : Disney Press, 2014)
Lightning McQueen is living in the fast lane - until he hits a detour and gets stranded in Radiator Springs; a forgotten town on Route 66. There he meets a heap of hilarious characters who help him discover there's more to life than fame.
Keywords: Automobiles -- Fiction; Automobiles, Racing -- Fiction; Friendship -- Fiction; Film novelizations